(untitled) (Research, Society and Development, 2021)
Worldwide, Tectona grandis (teak) is recognized for its productivity and the quality of its wood. The Brazilian market is already seen as a great potential for consumption and production of teak wood. Therefore, the objective of this work was to characterize the teak wood grown in Brazil through a bibliographic survey of the results already available. In general, it was found that the teak wood planted in Brazil has a certain variability in its technological properties, and these variations are due to the origin, genetic material, age, planting location and the cycle used in the management of the forest. In a way, we still do not have much research on the quality of teak wood, and it would be important to implement research programs and experiments that consider the different genetic materials, growing environments, planting spacing, silvicultural tracts and ages of cutting, to allow greater knowledge about the growth and the factors that can influence the quality of the wood to be produced.